Rift Valley fever virus and Coxiella burnetii infections among febrile patients, Eastern Ethiopia. - Dadi Marami; Adane Mihret; Nega Assefa; Alemseged Abdissa; Mahlet Osman; Gizachew Gemechu; Jacob S Witherbee; Adargachew Mulu; Rea Tschopp (PLoS Neglected Tropical Diseases)
Background Rift Valley fever (RVF) virus and Coxiella burnetii infections are significant public health concerns in East Africa, causing recurring outbreaks. However, the prevalence of these pathogens among febrile patients in Ethiopia remains unknown. This study aimed to determine the prevalence and associated factors of these infections among febrile patients. Methods A multisite cross-sectional study was conducted among 415 randomly selected adult febrile patients from health facilities in Shinile and Dire Dawa, Ethiopia, between March 01, 2023, and February 28, 2024. Serum samples were tested for the presence of antibodies against RVF virus and C. burnetii infections using various Enzyme Linked Immunosorbent Assays. Polymerase Chain Reaction (PCR) was used to detect RVF virus RNA and C. burnetii DNA in blood samples. A multivariable logistic regression model was used to identify predictive factors. A p value <0.05 was considered statistically significant. Results Of the 402 serum samples analyzed, 21 (5.2%) tested positive for immunoglobulin G (IgG) antibodies against RVF virus, and 86 (21.4%) tested positive for C. burnetii Phase I and Phase II antibodies. No RVF virus IgM was detected. Among the C. burnetii antibodies positive sera, 6 (7.0%) were positive for Phase II IgG antibodies. No blood samples tested positive for RVF virus RNA or C. burnetii DNA. Febrile patients aged ≥35 years had significantly higher odds of RVF virus exposure (AOR: 3.1, 95% CI: 1.3-7.8). Females (AOR: 1.7, 95% CI: 1.1-2.9), rural residents (AOR: 2.4, 95% CI: 1.3-4.5), and febrile patients who disposed of dead animals (AOR: 2.6, 95% CI: 1.2-5.6) exhibited significantly higher odds of C. burnetii infection. Conclusions This study reveals significant but underrecognized exposure to RVF virus (5.2%) and C. burnetii (21.4%) infections among febrile patients. Risk factors for RVF included older age, whereas C. burnetii infection was associated with females, rural residents, and exposure to dead animals. Health authorities are advised to consider these infections in the differential diagnosis of fever, implement active surveillance, and target public health interventions.